A Comparative Approach to Margin of Appreciation in International Law. (21st June 2019) - Muhammad, Nasiruddeen
Abstract: This article appraises the doctrine of margin of appreciation as an analytical lens through which international disputes in general, and economic disputes in particular, could be arbitrated and settled. The doctrine is broadly understood in the arena of multilateral integration arrangements as 'a line at which international supervision should give way to a state party's discretion in enacting or enforcing its laws'. In this context, it entails the latitude or discretion afforded to domestic State organs by international judicial organs in determining the level and manner of individual national compliance with the international legal obligations. This article first traces the evolution of the doctrine of margin of appreciation in international law. Second, it examines the balancing function of the doctrine from both vertical (that is, balancing between sovereignty of States, on the one hand, and judicial powers of international courts and tribunals on the other hand, or deference) and horizontal (that is, balancing between private right or interest on one hand, and overall public interest on the other hand, or proportionality) dimensions. Third, the article analyses the application of margin of appreciation by international courts and tribunals. The central proposition of the article is that margin of appreciation is a suitable tool for analysing the application and reach of legal rights and could aid international tribunals to strike a balance vertically and horizontally between competing rights or obligations among parties to international disputes.